The pornography of confinement. Porn expressions about the coronavirus - Paula Sequeira-Rovira (Íconos)
This text analyzes videos that have erotized situations linked to COVID-19, in which the use of gloves, masks, alcohol gel, or protective gear have represented the context of the pandemic, and that are referred to here as “pornography of confinement.” The aim of this article is to explore the characteristics of this type of pornography and analyze the links between such videos and demands upon the biopolitical subject, who is to be responsible for their own health. Approximately twenty-seven videos from the website Pornhub were reviewed, with special attention to ten that were entitled The Cleanest Porn Ever. All these materials aim to promote “safe sex” based on social distancing, viewing pornography, or learning hygienic techniques to avoid infection. Diverse theories, news stories, and data on this topic were used in the analysis. Among the key findings, pornography of confinement reflects the liberal subjectivity, as the individuals represented are not interested in strengthening social ties or participating in cultural change but rather in attending to their own immediate and individual needs. Finally, it is concluded that reality is simplified in this type of pornography by connecting people with “positive” emotions, discarding the potential for change that entails ties to the collective.